Assessment of Power Quality Characteristics of Wind Farms - Estanqueiro, Ana (2013)
In this paper the main parameters to assess the power quality of grid embedded wind farms are presented. International standards to assess and quantify the power quality of grid connected wind turbines exist for some years now, and are here extrapolated to wind farms aggregates when possible being the correspondent methodologies identified in the document. Recently, the grid code requirements posed a novel challenge to this technologic area, particularly since they were issued with national or local objectives and without particular normalized global concerns. The form how the international standards are evolving in order to cope both with the power systems industry local requirements, but also with the global wind turbine manufacturers principles is addressed in the paper.